(untitled) (Carte Romanze, 2024)
The article intends to analyze Conon de Béthune’s songbook not to propose a chronological scansion of the texts, rather to offer a reasoned and coherent reading, from which emerges the centrality of his poetic experience commonly considered heterodox, and which instead should be seen as an attempt, apparently unsuccessful, to indicate an alternative to Chrétien de Troyes’ proposal of total submission of the Lover to the Lady and above all to Love. For this and for the experimentalism of form and content that characterizes his writing, Conon finds himself involved in a very dense, even polemical, dialogue with trouvères and troubadours.